MULTIMODAL DISCOURSE ANALYSIS OF VISUAL PROTEST ON CLIMATE CHANGE - Nadia Nurfaizah; Laily Maulida Septiana Harti (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This paper focuses on the correlation between visual and linguistic elements in the meaning-making of visual protests of the demonstration on climate change. This study examines how elements in multimodality can attract people’s respect through visual and linguistic elements or modes and convey the same meaning from creator to readers or viewers. Visual and linguistic elements collaboration in a framework for Multimodal Discourse Analysis to build meaning was called Intersemiotic Complementarity. The interplay between visual and linguistic elements will be analyzed with intersemiotic complementarity. Experiential intersemiotic complementarity can be done between visual and linguistic elements in dealing with the main topic area and the climate change issue. Data of this study is visual protest on climate change collected through Instagram accounts. As this study aims to understand the message of visual protests, a qualitative study was employed. The term intersemiotic complementarity is realized in the visual protest through the name intersemiotic repetition and intersemiotic synonym. intersemiotic repetition exists in the earth illustration and the color it is used, while the intersemiotic synonym can be seen through the earth illustration and the linguistics elements, meaning that both elements complement each other.